Role of ferroptosis and ferroptosis-related non-coding RNAs in the occurrence and development of gastric cancer - Lu, Ling; Chen, Bei; Xu, Yumeng; Zhang, Xinyi; Jin, Longtao; Qian, Hui; Wang, Yi; Liang, Zhao Feng (Frontiers in Pharmacology, 2022)
Gastric cancer (GC) is a malignant cancer of the digestive tract and is a life-threatening disease worldwide. Ferroptosis is a newly discovered form of regulatory cell death in recent years, which involves the accumulation of iron dependent lipid peroxides. It has been found that ferroptosis plays an important regulatory role in the occurrence, development, drug resistance and prognosis of GC. Noncoding RNA (ncRNAs) plays a critical role in the occurrence and progression of a variety of diseases including GC. In recent years, the role of ferroptosis and ferroptosis related ncRNAs (miRNA, lncRNA and circRNA) in the occurrence, development, drug resistance and prognosis of GC has attracted more and more attention. Herein, we briefly summarize the roles and functions of ferroptosis and ferroptosis related ncRNAs in GC tumorigenesis, development and prognosis. We also prospected the future research direction and challenges in future research of ferroptosis and ferroptosis.